Adoption of UTAUT 2 model in analyzing the use of electronic money - Fitri Rahmadhani; Perengki Susanto (Operations Management and Information System Studies, 2021)
ln recent years, new financiaI services has been using technoIogy as an intermediary. Every year transactions using eIectronic money continue to increase. This research was conducted related to the evaluation of the use of e-money in Padang City, West Sumatra. The purpose of this study was to evaIuate the use of e-money in Padang City. This research used UTAUT 2 model which influencing the use of electronic money in Padang, West Sumatra using quantitative methods with the Smart PLS 3 analysis with 250 respondents. The sampling in this study used the purposive sampling method. The results of this study indicate that from social influence (SI), hedonic motivation (HM), habit (HT), behavior intention (BI), and use behavior (UB) benefits of this research is that it provide recommendations related to the UTAUT 2 model which can be used as consideration for future development of electronic money